A qualitative study on the experiences and challenges of MBA students' engagement with a business research methods module. Issue 1 (17th March 2021) - Nzekwe-Excel, Chinny
Abstract : Purpose: Undertaking research as part of a business degree qualification undoubtedly enables students to develop practical and life-long skills. Nevertheless, students seem to find it challenging undertaking a research project. This study set out to explore the experiences of a group of MBA students who recently undertook their business and management research projects as part of their MBA degree program. Design/methodology/approach: The study was carried out in a UK higher education institution and is based on an MBA business and management research module. The purpose of the module is to enable learners to develop advanced-level independent research and critical problem-solving skills within a business context. The study adopted a qualitative approach to capture a broad mix of students' experiences and perceptions on the module. The sample includes previous MBA students on different cohorts and different nationalities. Findings: Outcomes of the study show that though students are stretched in the business and management project process they develop a diversity of skills required in the workplace while conducting their projects. The study findings also show that the practical implications of the students' projects and progressive support from their project supervisors contribute to the successful completion of their projects and subsequent attainment of their MBA degree. Originality/value: Outcomes of this study further reveal that undertaking business and management projects creates a rewarding learning experience for learners/students, develops confident graduates as well as enables effective applications of theory into practice.